Exploring the Teaching Growth and Development of College Teachers in the Context of Informatization - Qu, Na; Wang, Qinghui (Journal of Theory and Practice of Humanities Science, 2023)
This paper explores the issue of teaching growth and development of college teachers under the background of information technology. It analyzes and discusses five aspects, namely, education and teaching concept, teacher and teaching association, the growth path of college teachers, the direction of teaching development of college teachers, and strategies and suggestions for teaching innovation of college teachers. This paper argues that the growth and development of college teachers' teaching is a complex and dynamic process, which requires college teachers to constantly update and optimize their education and teaching concepts, pay attention to and satisfy students' learning needs and interests, select and use suitable teaching contents and methods, design and produce creative teaching forms and methods, explore and practice new or effective teaching models, and demonstrate and evaluate their teaching effects and quality, to realize the novelty or effectiveness of teaching and to improve or break through the level or level of teaching. This paper hopes to provide some useful methods and opinions for the growth and development of college teachers' teaching, as well as some useful bases and references for the research and evaluation of education.